Molecular characterization and genetic evolutionary relationship of Staphylococcus sciuri using 16S rRNA gene sequencing from non-venomous snake checkered keelback (Fowlea piscator, Schneider, 1799) from Western Madhya Pradesh, India - Sarsavan, Anil; Ishaque, Shehla; Lodha, Minal; Gupta, Asheeb (International Journal of Scientific Research in Biological Sciences, 2021)
The study aims to explore pathogenic bacteria from the oropharyngeal cavity of non-venomous checkered keelback (Fowlea piscator) snake and evaluate the antibiotic assay. Swabbing was done under the supervision of a trained herpetologist and samples were aerobically cultured on the nutrient agar. All distinct colonies were subjected to Gram-staining and different biochemical tests. Molecular characterizations were done using the Sanger sequence method. The sequencing results were assessed by using BLASTn to evaluate the similarity with other species. Its phylogenetic tree was mapped using the neighbor-joining algorithm in MEGA X software. Staphylococcus sciuri strains NCTC12103 were identified based on Gram staining, morphological character, biochemical test and genetic characterization. Staphylococcus sciuri strain NCTC12103 was sensitive to most of the broad-spectrum antibiotics (piperacillin, ciprofloxacin, levofloxacin, gentamicin, cefotaxime) except erythromycin was used for snakebite treatment. The present study proves that a pathogenic bacterium is present in the non-venomous snake oral cavity. The study results make it evident that Staphylococcus sciuri could be responsible for secondary infection after the bite from a checkered keelback (Fowlea piscator).